Vitamin D Enhances Alveolar Development in Antenatal Lipopolysaccharide-Treated Rats through the Suppression of Interferon-γ Production - Liu, Chengbo; Chen, Ze; Li, Wen; Huang, Lisu; Zhang, Yongjun (Frontiers in Immunology, 2018)
Bronchopulmonary dysplasia (BPD) is characterized by the premature arrest of alveolar development. Antenatal exposure to inflammation inhibits lung morphogenesis, thereby increasing the risk for the development of BPD. Here, we investigated whether vitamin D (VitD) enhances alveolar development in antenatal lipopolysaccharide (LPS)-treated rats, which is a model for BPD. We used an established animal model of BPD, and random assignment to the control group, LPS group, or LPS with VitD group. Levels of interferon (IFN)-γ and interleukin (IL)-4 were detected by real-time polymerase chain reaction and enzyme-linked immunosorbent assay. IFN-γ producing CD8+ T cells were assessed by flow cytometry, and the methylation status of the VitD-response element was analyzed by bisulfite sequencing PCR. 25-Hydroxyvitamin D levels were measured by liquid chromatography tandem mass spectrometry in maternal serum samples collected from 86 pregnant women in a prospective birth cohort enrolled from 2012 to 2013. Our results showed that VitD effectively alleviated the simplification of the lung alveolar structure in BPD rats and suppressed LPS-induced IFN-γ expression in the lung and spleen tissues. Further investigation revealed that VitD suppressed IFN-γ production in CD8+ T cells. Specifically, VitD increased the methylation percentage of the VitD-response element in the IFN-γ-promoter region and suppressed LPS-induced expression of IFN-γ. Additionally, we observed an association between maternal VitD exposure during pregnancy and neonatal IFN-γ levels in a prospective birth cohort, with a trend similar to that observed in the animal model. Our data suggested that supplementation of VitD could suppress IFN-γ production, resulting in improved alveolar development in an LPS-induced BPD rat model.